2018
DOI: 10.1016/j.bjorl.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for oropharyngeal dysphagia after prolonged orotracheal intubation

Abstract: Patients submitted to prolonged intubation who have risk factors associated with dysphagia and aspiration should be submitted to an early speech-language/audiology assessment and receive appropriate and timely treatment. The recognition of these predictive factors by the entire multidisciplinary team can minimize the possibility of clinical complications inherent to the risk of dysphagia and aspiration in extubated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 27 publications
7
45
0
15
Order By: Relevance
“…The main reason is due to the impact of cardiopulmonary bypass and intraoperative hypothermia on various organ functions. For the recovery of nutritional support after cardiac surgery in infants, in addition to overcoming the potential injury from cardiopulmonary bypass during the operation and subjection of the gastrointestinal tract to ischemia-reperfusion injury, oropharyngeal injury and swallowing dysfunction caused by tracheal intubation must also be evaluated and treated [ 9 , 10 ]. If feeding disorder after cardiac surgery is avoided, patients can effectively avoid hospital complications caused by the use of total parenteral nutrition, nasogastric tubes, or even fistulas, which can even speed up the patients’ recovery process [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main reason is due to the impact of cardiopulmonary bypass and intraoperative hypothermia on various organ functions. For the recovery of nutritional support after cardiac surgery in infants, in addition to overcoming the potential injury from cardiopulmonary bypass during the operation and subjection of the gastrointestinal tract to ischemia-reperfusion injury, oropharyngeal injury and swallowing dysfunction caused by tracheal intubation must also be evaluated and treated [ 9 , 10 ]. If feeding disorder after cardiac surgery is avoided, patients can effectively avoid hospital complications caused by the use of total parenteral nutrition, nasogastric tubes, or even fistulas, which can even speed up the patients’ recovery process [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated the clinical characteristics of PED on the basis of the medical condition for which endotracheal intubation was initiated, and showed quantification of dysfunction in the oral and laryngeal swallowing phases by using VFSS. Previous studies have identified many clinical factors associated with PED, although the results of those studies were controversial [2]; the use of fiberoptic endoscopic evaluations in patients with PED revealed that intubation duration was related to the incidence and severity of PED [1,2,18,19]. In our study, we noted a correlation between the severity of PED, especially the amount of RV, and the severity of clinical illness, similar to the findings of another study [20].…”
Section: Discussionsupporting
confidence: 87%
“…This reassuring finding will not necessarily carry forward to long-term speech, swallowing, and breathing outcomes given the duration for which COVID-19 patients have had endotracheal and tracheostomy tubes in situ (Fig. 1) [9,43]. Therefore, the high rate of dysphonia that we identified at the first cuff down trial (Table 2) requires further follow-up to determine whether we will see a significant laryngological rehabilitation burden.…”
Section: Laryngotracheal Sequelae Of Covid-19 Airway Managementmentioning
confidence: 94%